Effect of Potassium Iodide and Glutathione on Color Change and Remineralization Potential Induced by Silver Diamine Fluoride Application - Salma Mohammed ElSabaa; Ahmed El Banna; Dina Ahmed El Refai (Dentistry 3000, 2024)
Purpose: To evaluate the effect of applying potassium-iodide (KI) and glutathione (GSH) on silver-diamine fluoride (SDF) induced tooth discoloration as well as their effect on its remineralization potential.